Pengaruh Competence, Reward di Mediasi Perceived Organizational Support Terhadap Employee Engagement - Muhammad Dawam; Sintia Arsita; Rayhan Achmad; Ade Subakti; Retno Purwani Setyaningrum (Journal of Trends Economics and Accounting Research, 2023)
The development of the business world cannot be separated from the development of human resources. Human resources are an important aspect in a company to achieve a goal. Every organization has a target to be achieved to achieve the goals of a company. Organizations as managers of human resources who have the value of progress and organizational life. This type of research uses statistical analysis methods through the SPSS Version 25 application. This sampling uses a random sampling technique with a total of 129 respondents. This study aims to examine, examine, and obtain results how the influence of Competence, Reward, Perceived Organizational Support on Employee Engagement at PT. Kyoraku Blowmolding Indonesia.